Diagnoses for Nubensia, n. gen. (Diptera, Chironomidae, Chironomini), with the first full descriptions of the adult female and larva of N. nubens (Edwards, 1929) - Spies, Martin; Dettinger-Klemm, Andreas (Zootaxa, 2015)
A new genus, Nubensia Spies, is proposed for N. nubens (Edwards, 1929), n. comb., based on morphological evaluation of both adult sexes, the pupa and larva. The material studied includes name-bearing syntype specimens and the first reared associations linking three life stages for individual members of this species. The larva represents a unique morphotype previously described incompletely only from studies of subfossil chironomid remains. The problems with placement of the species in any previously established genus are discussed in detail, and various related issues in taxonomy and nomenclature are commented on. The verified distribution of N. nubens ranges from the British Isles and central Europe to the western Mediterranean, including northern Africa, with possible extensions to Turkey and central Asia. Larvae have been found on mostly coarse, variously covered substrates near the shores of lakes and banks of slowly flowing running waters, under both oligotrophic and eutrophic conditions.